Editorial The June 2026 issue of the International Journal of Economic Performance presents 10 articles focusing on critical global themes - Benhamida, Hichem (International Journal of Economic Performance (IJEP), 2026)
Dear Readers, It is with great pleasure that we present this new issue of our journal. Although rooted in Algeria, our publication stands as a genuinely international space for scholarly exchange. This issue bears witness to that vocation through the diversity of our authors’ origins, coming from France, Saudi Arabia, Nepal, Egypt, Malaysia, Nigeria, South Africa, and Canada. This issue brings together contributions addressing highly topical economic, financial, and managerial questions. European competitiveness in the face of the United States and China, large language models in service of financial inclusion, the trade-led growth hypothesis, internal audit and fiscal discipline in local governments, artificial intelligence in service of economic diversification in the Gulf, volatility spillovers in Macao’s gaming economy, cybersecurity as a driver of banking customer loyalty, organizational citizenship behavior, government expenditure and unemployment, and DSGE modeling of the North African banking sector: these themes together illustrate the richness and relevance of the work gathered in this issue. This diversity, both thematic and geographic, would not have been possible without the commitment of our editorial board. We express our deep gratitude to our associate editors for their rigorous scientific guidance, as well as to all our reviewers, whose expertise and rigor remain the foundation of our journal’s credibility. We also thank our editorial secretariat for its meticulous work, essential to the publication of every issue. We wish you a rich and stimulating read. The Editor-in-Chief Hichem Benhamida, Professor of Economics at the University of Boumerdes (ALPEC LAB). Boumerdes, June 30, 2026